A complementary use of information from space-based DInSAR and field measuring systems for operational monitoring purposes in open pit iron mines of Carajás mining complex (Brazilian Amazon region) - Paradella, W. R.; Mura, J. C.; Gama, F. F.; Santos, A. R.; Silva, G. G.; Galo, M. [UNESP]; Camargo, P. O. [UNESP]; Silva, A. Q. (Copernicus Publications, 2015)
Now spanning five simultaneous open-pit operations with exploration carried out through open pit benching, Carajás complex encompasses the world's largest iron reserves. Open pit mining operations in the area can lead to slope instabilities with risks to personnel, equipment and production due to intense excavations in rock products of low geomechanical quality, blasting practices and heavy precipitation. Thus, an effective prediction and management of surface deformations should be a key concern for the mining operations. The ground displacement monitoring techniques in Carajás include surface measurement techniques at discrete points (total station/reflective prisms) and over area using SSR (Slope Stability Radar, a ground based radar). On the other hand, DInSAR techniques are receiving relevance in the mining industry for reasons such a synoptic and continuous coverage without the need for ground instrumentation and a point-to-point good accuracy of measuring displacements (millimeter to centimeter scale) over a dense grid. Using a stack of 33 StripMap TerraSAR-X images acquired over Carajás covering the time span from March 2012 to April 2013, a monitoring approach is discussed based on the complementary use of information provided by DInSAR (DInSAR Time-Series and Persistent Scatterer Interferometry) and surface measuring techniques (total station/prisms, ground-based radar).
Keywords: Carajá's province; DInSAR time-series; Ground-based radar; Open pit iron mine; PSI; Rock slope monitoring; TerraSAR-X; Total station/prisms